PENGARUH DISIPLIN KERJA, KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA KARYAWAN (Studi Pada PDAM Tirta Moedal Kota Semarang) - Astrianty Hapsary, 14.05.51.0185; Murdiyanto, Agus (Students' Journal of Economic and Management, 2018)
This study aims to determine and analyze the influence of work discipline, compensation and motivation on employee performance of PDAM Tirta Moedal Semarang City. Population in this research is employees of PDAM Tirta Moedal Semarang City, with a total sample of 83 respondents. Sampling technique in this research is random sampling. Methods primary data collection method used is questionnaire and data analysis using multiple linear regression model.The results of this study show that the discipline of work, compensation and motivation has positive and significant effect on employee performance. Keywords: Work Discipline, Compensation, Motivation and Performance of employees.